didikan Moderasi dalam Islam - Ahdar Ahdar; Munirah Munirah; Musyarif Musyarif (Pascasarjana IAIN Sultan Amai Gorontalo, 2022)
This article aims to unravel the concept of moderation education in the Qur'an. The method used is a qualitative analysis method by reviewing the literature on the concept of moderation education in the Qur'an, as well as other references from several articles that are considered relevant and representative. The results of the study and discussion show that moderation education is a concept that educates not to be extreme, radical, and tolerant of religion. That is the characteristic of Islam. Islam always takes the middle way in its guidance. The peaceful, moderate, and tolerant face of Islam will have an impact on peace for mankind.